The economic behaviour of poly-drug users in the Western Cape: an analysis of pathways, prices, location and gender - Melis, Monique (School of Economics, 2017)
The use of illicit substances in South Africa has implications for the health and well-being of both the user and society at large. Improved data on the markets for illicit psychostimulants are imperative for supporting policy efforts to manage their use and provide support structures for those affected. This thesis is one of the few detailed studies on the South African drug market using quantitative methods. It expands on what is known about illicit substance markets by addressing aspects of the following questions: (1) What is known about the nature and scope of the methamphetamine, methaqualone and heroin markets? (2) What is known about the characteristics of poly-substance consumers? (3) What does the sequential pattern of substance initiation look like? (4) Why do poly-substance consumers report different inter- and intra-regional drug prices? (5) What issues need further research? As a first step towards answering these questions, a dataset of 337 poly-substance users from the Western Cape was analysed. Survey participants were sampled using a respondent-driven sampling technique – an approach useful for sampling hidden populations and efficiently, adjusting for associated sampling bias. The study found that methamphetamine prices tend to fluctuate across a heterogeneous consumer base, with a significant discount paid by females who were observed, on average, to pay 25% less for this substance. Methaqualone has less variation across consumers but showed significant price dissimilarities between the two sites included in the analysis, with respondents from Greenpoint paying, on average, 18% higher prices. This indicates a lack of pricing information being shared between the two sites. Heroin showed variation across consumers, although the data on this substance were limited. Furthermore, the results show that substance markets operate differently across intra-city locations. The key rationale for this include high transit costs incurred by suppliers (as drugs cannot be transported openly), high search costs incurred by consumers and the prevalence of information asymmetries between regions. This study brings light and understanding to a traditionally hidden market and highly dangerous market; however, far more data on the South African and African drug market is needed.